Introduction to psychology - Hilgard, Ernest R. (Ernest Ropiquet) 1904-2001; Atkinson, Richard C. (New York Harcourt Brace Jovanovich, Inc., 1975)
Introduces contemporary psychology to the beginning student.
Includes bibliographical references (pages [619]-639) and index.
Keywords: Psychology